Pattern of antimicrobial usage in livestock animals in south-western Nigeria (2015)
Resistance to antibiotics has continued to increase, placing future animal and human disease management in real danger. The developing countries characterised by widespread indiscriminate antibiotic use and in which ‘third-generation’ antibiotics are not readily available or affordable are the worst affected. A 3-year (2010–2012) retrospective survey of antibiotic usage in livestock production in three selected states of south-western Nigeria was conducted. Data obtained from eight purposively selected licensed veterinary pharmaceutical sales establishments in the area, based on keeping detailed sales records for the study period, were analysed using Stata Version 12. Results showed that tetracyclines (33.6%), fluoroquinolones (26.5%) and beta-lactams/aminoglycosides (20.4%) constituted the majority of the antibiotics used over the 3 years. The differences in the quantities of antibiotic types used within each antimicrobial class were statistically significant for tetracyclines (F = 59.87; p < 0.0001) and fluoroquinolones (F = 43.97; p < 0.0001) but not for beta-lactams/aminoglycosides (F = 3.21; p = 0.148). Furthermore, antibiotic consumption increased by 40.4% between 2010 and 2012. Although statistically insignificant (F = 0.277; p = 0.762), the increasing trend across the years was at rates of 23.5% between 2010 and 2011 and 13.8% between 2011 and 2012. In addition, the findings show a significantly higher consumption rate (t = 15.21; df = 5; p < 0.0001) during the rainy (52.5%) than the dry (47.5%) seasons. The current increasing trend in antibiotic usage holds a serious danger for the future and therefore calls for alternative plans to safeguard future livestock production, food security and human health. This becomes more imperative considering emerging resistance against tetracyclines and fluoroquinolones, the foremost remedies for livestock diseases in most developing countries.